Industrial Upgrading of Korea: Process and Prospect - Cheonsik Woo; Kwang-Eon Sul (Korea Development Institute (KDI), 2000)
After five decades of industrialization, Korea now resembles the major advanced economies in its basic industrial profile. But with industrial activities heavily concentrated in low to medium value added industrial activities such as processing and production, Korea remains behind these economies in the quality of its industrial structure. Except for a few elite firms that belong to Chaebols in select fields such as semiconductors and automobiles, Korean firms lack their own basis of competitiveness that is adequate to ensure their survival in the ever-accelerating wave of open, innovation-based, global competition. Korea must surmount huge obstacles to retain growth momentum in the medium term and to become a competitive, knowledge-based economy with sound fundamentals in the long term. What are the potentials of Korean industry and what policies are needed to realize them? Addressing these questions, this paper briefly reviews Korea's industrialization process to date and suggests that Korea's industrial basis today need to be characterized and assessed from a dynamic, comprehensive perspective. It diagnoses the limits and potential of Korean industries in the context of the rising trends of global competition and co-operation and discusses the basic direction of industrial upgrading as well as the requisite policy measures. Stressing the importance of promoting small- and medium-sized companies in particular, the paper suggestively sets forth a practical proposal for establishing a cluster of firms in the machinery industry-both to upgrade this core industry to compete in the environment of the twenty-first century and to provide a new model of industrial and regional development for other Korean industries to follow.
Keywords: 330